2021
DOI: 10.1182/bloodadvances.2021004580
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of acute lymphoblastic leukemia with KMT2A (MLL) rearrangement: the MD Anderson experience

Abstract: Acute lymphoblastic leukemia (ALL) with t(4;11)(q21;q23) - KMT2A-AFF1 is associated with a poor prognosis. The impact of KMT2A rearrangements other than t(4;11) is uncertain and the benefit of allogeneic stem cell transplant (HSCT) is unclear. We reviewed adult patients with ALL treated at our institution from 1984 to 2019 and identified 50/1102 (5%) with KMT2A rearrangement: 42 (84%) with t(4;11)/KMT2A-AFF1 and 8 (16%) with other gene partners. The median age was 45 years old (range, 18 - 78 years); median wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In this article, MLL rearrangements were identified as an important prognostic factor in adult ALL. MLL -rearranged ALL ( MLL -r-ALL) is related to aggressive biology with early relapse, a relative high incidence of central nervous system leukemia (CNSL) involvement, and poor prognosis ( 7 , 40 ). The incidence of MLL -r-ALL is bimodal and increases with age in adults ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this article, MLL rearrangements were identified as an important prognostic factor in adult ALL. MLL -rearranged ALL ( MLL -r-ALL) is related to aggressive biology with early relapse, a relative high incidence of central nervous system leukemia (CNSL) involvement, and poor prognosis ( 7 , 40 ). The incidence of MLL -r-ALL is bimodal and increases with age in adults ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…KMT2Ar constitutes 5% of ALL and 8% of MPAL diagnoses. 20 With regard to risk stratification in adults, apart from KMT2A with the fusion partner t(9;11) (p21.3;q23.3) that is classified as intermediate-risk feature, 21 the presence of KMT2Ar in conjunction with other fusion partners confers poor prognosis with long-term overall survival rates of ≤10% following standard intensive chemotherapy. Patients are typically referred for allogeneic SCT in first remission following upfront therapy.…”
Section: Kmt2a Rearranged Acute Leukemiasmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) bearing the KMT2A‐rearrangement is a high‐risk genomic subgroup, characterized by chemotherapy‐resistance and a propensity for rapid relapse with reported 5‐year overall survival of less than 20% 1 . Unique in its involvement in early leukemogenesis, KMT2A gene rearrangement has been described to confer overlapping immunophenotypic features of both myeloblasts and lymphoblasts, hence previously known as the mixed‐lineage leukemia (MLL) gene.…”
Section: Reference [Year] Age Prior No Of Crs Unique Molecular Charac...mentioning
confidence: 99%
“…A review of the past 8 years since the FDA's initial approval of blinatumomab identified 33 reported cases, 17 with blinatumomab and 16 with an anti-CD19 CAR-T cell therapy (Table 1). [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The median [IQR] number of prior CRs was 1 [1,2] (among those reported) with time to LS occurring within 12 months in 90.9% of patients. Of significance, the KMT2A-rearrangement was implicated in 81.8% of cases-88.2% with blinatumomab and 75% with a CAR-T immunotherapy.…”
mentioning
confidence: 99%